Suppression of lipopolysaccharide and hydrogen peroxide-induced inflammatory responses in raw 264.7 macrophage by pleurotus giganteus and lignosus rhinocerotis / Asweni a/p Baskaran - Baskaran, Asweni (2015)
Inflammation is the most important host defence mechanism that protects the body against pathogenic challenges. Inflammation has been linked to the pathogenesis of various diseases such as diabetes, Alzheimer’s, cardiovascular and cancer. Further, these diseases are currently the leading cause of death among humans. The search for anti-inflammatory food is on-going and the mushrooms are being recognised as nutritional and functional foods that may reduce inflammation. Pleurotus giganteus and Lignosus rhinocerotis are commercially grown in Malaysia. In the present study, the in-vitro anti-inflammatory activity of ethanol and hot aqueous extract of P. giganteus and L. rhinocerotis were evaluated for the ability to inhibit lipopolysaccharide (LPS)-induced nitric oxide (NO) production and down regulation of the inflammatory markers. The effects of ethanol extracts of P. giganteus on LPS and hydrogen peroxide (H2O2) - induced NO production, inducible nitric oxide synthase (iNOS) and glutathione peroxidase (GPx) expression were investigated to correlate inflammation and oxidative stress. The ethanol extract of P. giganteus (EPG) (10 μg/ml) showed the highest reduction of 74.7 % of lipopolysaccharide (LPS)-induced NO production in RAW 264.7 macrophage while ethanol extract of L. rhinocerotis (ELR) (100 μg/ml) showed the highest reduction of 88.51%. Hence, EPG was chosen for the gene expression study as it showed higher reduction at a lower concentration (10 μg/ml) compared to ELR (51.4 %). Further, EPG showed a 2.7 fold down regulation of inducible nitric oxide synthase (iNOS) and significantly suppressed (p < 0.05) the expression of signal transducer and activator of transcription 3 protein (STAT 3) in LPS-stimulated murine RAW 264.7 macrophage. Ethanol extract of P. giganteus (EPG) also exhibited a significant inhibitory (p < 0.05) effect on LPS and H2O2-induced NO production (28.7 %). Ethanol extract of P. giganteus (EPG) showed a 2.4 and 8.5 fold down regulation of the LPS and H2O2-induced inducible nitric oxide synthase (iNOS) and GPx expression respectively.